Online Consumer Purchase Decision of Alcohol Products in Sri Lanka - Senevirathne, Muhandiram Arachchilage Ruchira Savinda (2024)
This study investigates the changing aspects of online purchasing decisions within Sri Lanka's alcohol industry, focusing on the Colombo district. Directed by specific objectives, including the impacts of advertising, pricing, social factors, and perceived risks, a deductive approach with a Positivism philosophy was employed to gather, analyze, and draw conclusions from data collected from over 6000 online consumers. Utilizing simple random sampling, 361 respondents were surveyed via an online questionnaire, with data analyzed through descriptive, factor, reliability, and correlation analyses using SPSS. Results indicate a male dominated demographic aged 30 to 34 engaging in online purchases, with advertising significantly influencing brand preference, albeit messaging playing a minor role. Price emerged as a minimal factor, though discounted offers garnered interest, and social recommendations strongly influenced purchasing decisions. The study concludes that advertising, pricing, perceived risk, and social factors are directly correlated with consumer purchasing decisions, with recommendations emphasizing tailored messaging across diverse media channels, competitive pricing strategies, and a focus on social dynamics and cultural adaptation within the industry.